Miseducation : inequality, education and the working classes - Reay, Diane (21st Century Standpoints, 2017)
This book brings Brian Jackson and Dennis Marsden's pioneering Education and the Working Class from 1962 up to date for the 21st century and reveals what we can do to achieve a fairer education system.